MENUJU DESA MANDIRI: INOVASI DAN STRATEGI PEMERINTAH DESA BOJONG KULUR - Kariena -; Ersa Falena Fitri (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Bojong Kulur Village is one of the villages that holds the status of Independent Village based on the Village Development Index (IDM). Bojong Kulur Village has maintained its Independent Village status since 2016. In 2022, this village was awarded as an Independent Village with the 5th highest IDM ranking in West Java. This study seeks to explore the strategy of the Bojong Kulur Village government in realizing an independent, prosperous, and beautiful village by optimally managing local potential, reducing external dependency, and encouraging high achievement in Social, Economic, and Ecological Resilience indicators. Using Geoffrey Mulgan's strategy theory, which covers five aspects: objectives, environment, direction, action, and learning. Qualitative descriptive methods were used in the research through observation and interviews. The results show that Bojong Kulur Village has a vision and mission that describe the ideal conditions it wants to achieve, such as improving community welfare and economic independence. These goals serve as guidelines in designing village development policies and programs. Bojong Kulur Village is able to identify potential resources, social, economic, educational, and health sectors, as well as existing challenges. The village government has been able to determine policy directions in accordance with existing procedures and has involved various stakeholders, the community, and the Youth Organization (Karang Taruna). The village government has conducted a process of evaluation, reflection, and continuous learning from program implementation experiences, enabling the village to refine its strategies and adapt to change. This learning strengthens the village's capacity to face challenges and enhances the effectiveness and sustainability of its programs.